Venture Capital in Bank- and Market-based Economies - Adeline Saillard; Thomas Url (Austrian Institute of Economic Research (WIFO), 2011)
The determinants of venture capital investment have attracted a significant amount of attention from both academics and policymakers. We use a version of the Keuschnigg-Nielsen model for venture-capital financed projects to condition our analysis on a reasonable set of exogenous variables but we focus on one determinant: financial market structure. The type of financial market structure (bank- or market-based) contributes substantially to explaining differences among countries with respect to the extent of venture capital investments in the initial business stages. We will use the cross country and time series variation from a panel of 19 industrialised countries to support the hypothesis that venture capital thrives within market-based financial systems and is confined to an ancillary role in bank-based systems.
Keywords: 330; Venture capital; financial market structure; local stock markets; panel data; Risikokapital; Investition; Finanzsektor; Institutionelle Infrastruktur; Vergleich; Industrieländer; Welt